Analisis Kimia Dan Organoleptik Tepung Ubi Banggai (Dioscorea alata) Pada Variasi Perendaman - Chaniago, Ramadhani; Handila, Moh. Asyroto; Lamusu, Darni (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
In making Banggai yam flour, the best method and quality of flour on a standard production scale has not yet been found. Therefore, it is necessary to carry out research and innovation in order to obtain the best formulation for standard Banggai yam flour. One of the research innovations that was attempted was various methods of soaking the Pride yam before making flour. The aim of this research was to obtain the best results in several types of soaking on the chemical and organoleptic characteristics of Banggai yam flour. The method used was a Completely Randomized Design research with 4 immersion treatments with 3 replications, into 12 experimental units, namely: P1 = water; P2 = whiting solution; P3 = lactic acid solution; P4 = sodium metabisulfite solution. The variables of this research are proximate tests and organoleptic tests. The conclusions of this research are: In the proximate test results and gluten content, treatment P1 is the best in water and carbohydrate content, namely 12.48% and 79.04% respectively, then treatment P2 is the best in producing fat and gluten, namely 0.31% and 1.01%. Furthermore, the P3 treatment was the best in terms of ash and protein content, namely 2.14% and 10.45% respectively. In the organoleptic test results, Banggai yam flour, namely the P3 treatment, gave the best results in the color, aroma, texture and overall liking test for Banggai yam flour.